The Bulgarian Tax System in the Context of the European Union Countries: Comparative Aspects - Nenkova, Presiana; Nikolova, Velichka; Angelov, Angel (Research Papers, 2025)
The current study examines the Bulgarian tax system in the context of the European Union countries. Through an analysis of the values of fiscal indicators measuring the tax burden and illustrating the tax structure, and of their change in the period 1995-2022, Bulgaria's position in relation to the countries of the European Union is highlighted and the effects of the tax policy pursued on the structure of tax revenues in Bulgaria are traced. In the course of the study, the applied tax policies in time of crises are also examined with an emphasis on the role and importance of the tax reliefs used. The main conclusions reached are related to the achievement of a lower tax burden in Bulgaria compared to most EU countries, which is mainly due to the taxation stemming from direct taxes, while at the same time there is a higher tax burden on consumption, but also a relatively low share of tax expenditures in GDP and budget revenues.
Keywords: Tax policy; Taxes; Bulgaria; European union